2010
DOI: 10.1371/journal.pone.0011578
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Uric Acid Increases the Risk for Nonalcoholic Fatty Liver Disease: A Prospective Observational Study

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a common form of chronic liver disease, and serum uric acid is observed to be significantly elevated in NAFLD patients. However, whether this elevation is causal, a bystander, or a consequence of NAFLD remains unclear. We performed a population-based prospective study among the employees of Zhenhai Refining & Chemical Company Ltd., Ningbo, China to investigate whether the elevation of serum uric acid has a casual role for NAFLD. A total of 6890 initially NAFLD-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
133
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(154 citation statements)
references
References 33 publications
(36 reference statements)
13
133
0
4
Order By: Relevance
“…This may be because high UA indicates ongoing hepatocellular destruction. So far, most of the studies on serum UA have been done with NAFLD 10 . In one prospective study from China, they found that hyperuricemia was an independent predictor of development of NAFLD with hazard ratio of 1.62 10 .…”
Section: Discussionmentioning
confidence: 99%
“…This may be because high UA indicates ongoing hepatocellular destruction. So far, most of the studies on serum UA have been done with NAFLD 10 . In one prospective study from China, they found that hyperuricemia was an independent predictor of development of NAFLD with hazard ratio of 1.62 10 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a graded, positive association between SUA levels and NAFLD severity and elevated SUA levels predict NAFLD risk independently of coexisting MetS features in different ethnicities. [99][100][101][102][103][104][105][106][107][108] Accordingly, a large study found that increased SUA levels were associated with cirrhosis and elevated serum liver enzymes, independent of potential confounders, in 5,518 participants during a mean follow-up of 12.9 years. 96 Further studies are needed to ascertain whether reducing SUA levels would prevent NAFLD/NASH development and progression.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Another study also indicated that hypouricemic therapy using allopurinol and benzbromarone significantly ameliorated hepatic steatosis and decreased serum cholesterol levels in a Mongolian gerbil model of NAFLD (19). In fact, a population-based prospective study showed that SUA was significantly associated with the development of NAFLD, suggesting that high SUA levels may have a causal role in the development of NAFLD (9). Similarly, the present study demonstrated that the SUA level was significantly associated with the degree of steatosis from a histological perspective.…”
Section: Discussionmentioning
confidence: 98%
“…Hyperuricemia was significantly associated with NAFLD, and the prevalence of NAFLD increases with SUA increase (6)(7)(8). Elevation in SUA levels independently predicts an increase in the risk for the incident of NAFLD and suggests that high SUA levels may have a causal role in the development of NAFLD (9). Certain in vitro and in vivo studies in hepatocytes and liver tissue of mice suggest that uric acid stimulated fat synthesis and induced inflammatory cell infiltration in the liver (10,11).…”
Section: Introductionmentioning
confidence: 96%